2007
DOI: 10.1177/0734371x07307076
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Manager . . . Takes a Break

Abstract: This study examines how senior local government managers take work breaks and how doing so is associated with perceptions of performance. Three purposes of taking a break are studied: (a) to reflect on prior work, (b) to restore oneself physically and mentally, and (c) to take care of personal, nonwork needs. On average, managers take a few breaks every week, lasting about 15 min each. Only about 45% of managers agree or strongly agree that break-taking helps them to reduce stress, clear their mind, make them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…WORK BREAKS SYSTEMATIC REVIEW frequency of work breaks (Berman & West, 2007), the recovery experiences during or immediately after work breaks (Bosch et al, 2018;Coffeng et al, 2015;Demerouti et al, 2012), and break activities (Kühnel et al, 2020;Trougakos et al, 2014;von Dreden & Binnewies, 2017), including microbreak strategies (e.g., Kim et al, 2017;Schulz et al, 2017;Zacher et al, 2014).…”
Section: Conceptualizing Work Breaksmentioning
confidence: 99%
See 2 more Smart Citations
“…WORK BREAKS SYSTEMATIC REVIEW frequency of work breaks (Berman & West, 2007), the recovery experiences during or immediately after work breaks (Bosch et al, 2018;Coffeng et al, 2015;Demerouti et al, 2012), and break activities (Kühnel et al, 2020;Trougakos et al, 2014;von Dreden & Binnewies, 2017), including microbreak strategies (e.g., Kim et al, 2017;Schulz et al, 2017;Zacher et al, 2014).…”
Section: Conceptualizing Work Breaksmentioning
confidence: 99%
“…An Integrative Framework of Work Breaks relatively short, similarly taking about 15 min (Berman & West, 2007). Studies that examine the duration of social media breaks report that the time per work hour spent on social media for nonwork purposes is relatively modest (average of 4.54 min in an hour); however, this time adds up to a substantial amount when considered over the entire workday (Kühnel et al, 2017;.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Berman and West (Berman, 2007) contemplated the functions that may be included in a scheduled work day break. It was revealed that several management skill functions were associated with senior local government managers (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Given that there is substantial evidence to suggest that "a break" can increase efficiency (e.g. Berman and West, 2007;Carlin, 1997), much of this behaviour has to do with perceptions and securing the right kind of identity within the professional environment of a large accounting firm. It is one thing to be efficient, but something else entirely to be seen as efficient.…”
mentioning
confidence: 99%